The Difficulty Factors of Students to Understand Mathematics Physics 1 at Physics Education Department FKIP Unsyiah - Bustami Bustami; Ngadimin Ngadimin; Ahmad Farhan (Universitas Syiah Kuala, 2020)
This study aims to determine the factors that cause college students to experience difficulty in understanding Mathematics Physics I lectures and any material / subject from Mathematics Physics I subjects that college students experience difficulties. This research uses a qualitative approach. The subjects in this study were college students of FKIP Unsyiah Department of Physics Education 2017 with a population of 50 people . Data collection techniques through questionnaires (questionnaire) and interviews. The results of the study concluded that college student factors, KBM factors, and learning facility factors did not cause college students to experience difficulties in understanding Mathematics Physics I lectures and overall Mathematics Physics I material / subjects were less difficult for college students to understand. .Kata Kunci : Learning Difficulties, Physics Mathematics I